Iron Oxide/Polymer‐Based Nanocomposite Material for Hydrogen Sulfide Adsorption Applications. Issue 11 (8th October 2014) - Blatt, Oliver; Helmich, Martin; Steuten, Bastian; Hardt, Sebastian; Bathen, Dieter; Wiggers, Hartmut; Schlücker, Eberhard
Abstract The processing of iron oxide nanoparticles derived from spray flame synthesis for specific adsorption applications is described. After the as‐prepared particles proved the ability for H2S removal in pure gas treatment, two different nanoparticle‐based composite materials were prepared. While impregnation of activated carbon with the as‐prepared nanoparticles showed the expected increase in H2S adsorption capacities, a significant enhancement in desulfurization performance was observed for a novel iron oxide nanoparticle composite material. H2S adsorption was tested in fixed‐bed breakthrough curve measurements. The H2S removal efficiency of the novel material under ambient conditions indicates highly promising properties for potential use in industrial and air pollution control applications.